# How does $P(C > D \mid C = 2) \neq P(C > D \mid C \neq 2)$ prove that B > C depends on C > D?

I grok that $\color{limegreen}{P(C > D \mid C = 2) = P(D = 1 \mid C = 6) = 1/2}$, and $\color{red}{P(C > D \mid C \neq 2) = P(C > D \mid C = 6) = 1}$. But I don't grok the last sentence in the quotation below, colored in blue. How do these two probabilities prove that B > C DEPENDS ON C > D?

- Consider four nonstandard dice (the Efron dice), whose sides are labeled as follows (the 6 sides on each die are equally likely).
A: 4; 4; 4; 4; 0; 0

B: 3; 3; 3; 3; 3; 3

C: 6; 6; 2; 2; 2; 2

D: 5; 5; 5; 1; 1; 1These four dice are each rolled once. Let A be the result for die A, B be the result for die B, etc.

(a) Find P(A > B), P(B > C), P(C > D), and P(D > A).

(b) Is the event A > B independent of the event B > C? Is the event B > C independent of the event C > D? Explain.

## Solution:

Blitzstein, *Introduction to Probability* (2019 2 edn), Ch 2, Exercise 30, p 88. pp 13-14 in the publicly downloadable PDF of curbed solutions.

## 1 comment thread